Classification of Chronic Pain at a Multidisciplinary Pain Rehabilitation Clinic - Jan Lidbeck; Gertie IM Hautkamp; Ritva A Ceder; Urban LO Näslund (Pain Research and Management)
OBJECTIVE: To make a detailed diagnostic analysis of patients with chronic pain syndromes, including classification according to the International Association for the Study of Pain (IASP).